A Retrospective Paired Comparison Between Untargeted Next Generation Sequencing and Conventional Microbiology Tests With Wisely Chosen Metagenomic Sequencing Positive Criteria - Qin, Hanyu; Peng, Jinmin; Liu, Ling; Wu, Jing; Pan, Lingai; Huang, Xiaobo; Huang, Man; Qiu, Haibo; Du, Bin, The China Critical Care Clinical Trials Group (CCCCTG) (Frontiers in Medicine, 2021)
Objectives To evaluate the performance of metagenomic next generation sequencing (mNGS) using adequate criteria for detection of pathogen in lower respiratory tract (LRT) samples with paired comparison to conventional microbiology tests (CMT). Methods 167 patients were reviewed from 4 different ICUs in mainland China during 2018 with both mNGS and CMT results of LRT samples available. RPM (sample/NTC) ratio and SDSMRN were the 2 criteria chosen identifying positive pathogen reported from mNGS. McNemar test was used for paired comparison analysis between mNGS and CMT. Results 149 cases were counted into final analysis. RPM ratio criterion performed better with a higher accuracy for bacteria, fungi and virus than SDSMRN criterion (bacteria [RPM ratio vs. SDSMRN], 65.1% vs. 55.7%; fungi, 75.8% vs. 71.1%; DNA virus, 86.3% vs. 74.5%; RNA virus, 90.9% vs. 81.8%). mNGS was superior in bacteria detection only if using SDSMRN ≥3 as positive criterion with a paired comparison to culture (SDSMRN positive, 92/149[61.7%]; culture positive, 54/149[36.2%]; p<0.001) but outperformed with significantly more fungi and DNA virus identification by choosing both criteria for positive outliers(fungi[RPM ratio vs. SDSMRN vs. culture], 23.5% vs. 29.5% vs. 8.7%, p<0.001; DNA virus[RPM ratio vs. SDSMRN vs. PCR], 14.1% vs. 20.8% vs. 11.8%, p<0.05). Conclusion mNGS may contribute to revealing LRTI etiology in the hospitalized group of potential fungal infections and in situation with less access to multiplex PCR of LRT samples from the laboratory by choosing a wise criterion like RPM (sample/NTC) ratio.